The symbolic signs of a photographic image of the Anfal genocide - فەتحوڵا, أ.د.ئیبراهیم سەعید فەتحوڵا; رۆستم, فتاح محمود رۆستم (Sulaimani Journal for Humanities, 2025)
This study is an attempt to be aware of the symbolic signs in a photograph taken in the castle (Nzake) of Duhok province during the Anfal genocide. The purpose of this study is to present the symbols that are in the photograph, for this purpose, based on the method of qualitative analysis of symbolism, which is one of the methods to determine the various signs of the photography on the visible and invisible levels, has reached several conclusions, including: the symbolic signs of the Photograph in terms of visualization shows that the Anfal process was comprehensive did not distinguish between men and women, children, old and young. The mental state of the detainees is unusual and uncertain.
Keywords: Photography; Simo logy; Anfal; Genocide